Geography at the Universitat Autònoma de Barcelona: A project of Enric Lluch (I) - Tulla Pujol, Antoni F.; Garcia Ramon, Maria Dolors; Estalella Boadella, Helena (Documents d’Anàlisi Geogràfica, 2019)
Geography has been taught at the Autonomous University of Barcelona (UAB) for 50 years (1969-2019). This paper explores the first 20 years of geography until the entry into force of the University Reform Law (LRU) at the UAB and the academic team that accompanied Enric Lluch (1928-2012) in this experience. The introduction of geography based on innovative approaches coming mainly from France, English-speaking countries and Italy is discussed. The programs of study in which geography is taught at the Faculty of Philosophy and Letters, the training seminars and the first investigations are also described. The story begins with the personal and academic experiences of two female teachers and a male teacher who formed part of the initial team, and then focuses on the main features of the department, from governance to the consolidation of geography at the UAB as an academic discipline and as a way of understanding society and the territory. It is an opportunity to explain the foundational stage as a significant historical period for the subsequent creation of the Geography Department at the Universitat Autònoma de Barcelona.